Associations of Platelet Indices with Body Fat Mass and Fat Distribution. Issue 10 (27th September 2018) - Han, Shuang; Gan, Da; Wang, Guowei; Ru, Yuan; Huang, Chao; Lin, Jie; Zhang, Liang; Meng, Zhuoxian; Zhu, Shankuan
Abstract : Objective: This study was undertaken to investigate the associations of platelet indices with body fat, including body fat mass and fat distribution. Methods: A total of 3, 327 individuals aged 18 to 80 were enrolled. Body fat was assessed by dual‐energy x‐ray absorptiometry. Blood samples were collected to measure platelet indices (platelet count [PLT], plateletcrit [PCT], mean platelet volume, platelet distribution width, and platelet large cell ratio). Adjusted multivariate linear regression models were used to identify the associations of platelet indices with body fat. Results: PLT was positively associated with BMI, waist circumference, waist‐hip ratio, total fat mass percentage, trunk fat mass percentage, android fat mass percentage, and android to gynoid fat ratio but negatively associated with gynoid fat mass percentage, total lean mass percentage, and skeletal muscle mass index. Similar associations were found between PCT and body fat. However, no significant associations were found between the other three platelet indices and body fat. Conclusions: Both PLT and PCT were associated with body fat, and the associations depended on fat location. Because PCT is mainly influenced by PLT, these associations suggest that platelet quantity is more closely related to body fat mass and fat distribution.